Dual bioactivities of laurus nobilis essential oil / Nur Afiqah Saparin ... [et al.] - Saparin, Nur Afiqah; Mahat, Mohd Muzamir; Zainal Ariffin, Shahrul Hisham; Mohamad Ali, Nor Azah; Safian, Muhd Fauzi; Zainal Ariffin, Zaidah (Faculty of Applied Sciences, 2020)
The evolution of cosmetic products results in the growing demands for cosmetics that are preservatives free. Plant essential oils were found to be a promising antimicrobial and also antioxidant agent. In this study, Cymbopogon citratus (lemongrass), Laurus nobilis (bay leaf) and Backhousia citriodora (lemon myrtle) essential oils were selected and evaluated for their antimicrobial properties. It was found that Laurus nobilis exhibited strong antimicrobial activity against the selected bacteria Streptococcus saprophyticus (ATCC 49619), Streptococcus aureus (ATCC 22923), Streptococcus pyogenes (ATCC 29436), Pseudomonas aeruginosa (ATCC 13048), Klebsiella pneumoniae (ATCC 700603), Escherichia coli (ATCC 22922) with MIC ranging between 7.8 ug/mL to 250 μg/mL. The antioxidant activity of selected essential oils was determined by antioxidant assays which were 1,1-Diphenyl-2-picrylhydrazyl assay (DPPH), determination of ferric reducing antioxidant power assay (FRAP) and β-Carotene/linoleic acid bleaching assay. Backhousia citriodora and Laurus nobilis showed the highest antioxidant activity. n-Octanal and β-Selinene were identified to be the major components with peak area of 26.37 % and 13.92 % respectively in secondary metabolites analysis by Gas Chromatography-Mass Spectrometry (GCMS).